A The Effect of Current Ratio and Debt to Equity Ratio on Earnings Growth with Company Size as a Moderating Variable - Ummu Azhar Fadillah; Edi Joko Setyadi; Sri Wahyuni; Rezky Pramurindra (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of Current Ratio and Debt to Equity Ratio on profit growth, with firm size as a moderating variable, in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The research employs a quantitative approach, using Moderated Regression Analysis (MRA) as the data analysis technique. A total of 101 samples were obtained through purposive sampling. The analysis results indicate that the Debt to Equity Ratio has a negative effect on profit growth, while the Current Ratio has no significant effect. Furthermore, firm size is proven to moderate the effect of the Debt to Equity Ratio on profit growth, but it does not moderate the relationship between the Current Ratio and profit growth. This research provides a theoretical contribution to the development of financial literature and offers practical insights for company management and investors in making strategic decisions.